Petrological constraints on the tectonic setting of the Kathmandu Nappe in the Langtang–Gosainkund–Helambu regions, Central Nepal Himalaya. (20th September 2016) - Rapa, G.; Groppo, C.; Mosca, P.; Rolfo, F.
Abstract: The Gosainkund–Helambu region in central Nepal occupies a key area for the development of Himalayan kinematic models, connecting the well‐investigated Langtang area to the north with the Kathmandu Nappe (KN), whose interpretation is still debated, to the south. In order to understand the structural and metamorphic architecture of the Greater Himalayan Sequence (GHS) in this region, a detailed petrological study was performed, focusing on selected metapelite samples from both the Gosainkund–Helambu and Langtang transects. The structurally lowest sample investigated belongs to the Lesser Himalayan Sequence; its metamorphic evolution is characterized by a narrow hairpin P–T path with peak P–T conditions of 595 ± 25 °C, 7.5 ± 1 kbar. All of the other samples here investigated belong to the GHS. Along the Langtang section, two tectono‐metamorphic units have been distinguished within the GHS: the Lower Greater Himalayan Sequence (L‐GHS), characterized by peak P–T conditions at 728 ± 11 °C, 10 ± 0.5 kbar (corresponding to a T/ depth ratio of 22 ± 1 °C km −1 ), and the structurally higher Upper Greater Himalayan Sequence, with peak metamorphic conditions at 780 ± 20 °C, 7.8 ± 0.8 kbar (corresponding to a T/ depth ratio of 31 ± 4 °C km −1 ). This confirms the existence of a main tectono‐metamorphic discontinuity within the GHS, as previously suggested by other authors. The results of petrological modelling of the metapelites from the Gosainkund–Helambu section show that this region is entirely comprised within a sub‐horizontal and thin L‐GHS unit: the estimated peak metamorphic conditions of 734 ± 19 °C, 10 ± 0.8 kbar correspond to a uniform T/ depth ratio of 23 ± 3 °C km −1 . The metamorphic discontinuity identified along the Langtang transect and dividing the GHS in two tectono‐metamorphic units is located at a structural level too high to be intersected along the Gosainkund–Helambu section. Our results have significant implications for the interpretation of the KN and provide a contribution to the more general discussion of the Himalayan kinematic models. We demonstrate that the structurally lower unit of the KN (known as Sheopuri Gneiss) can be correlated with the L‐GHS unit; this result strongly supports those models that correlate the KN to the Tethyan Sedimentary Sequence and that suggest the merging of the South Tibetan Detachment System and the Main Central Thrust on the northern side of the KN. Moreover we speculate that, in this sector of the Himalayan chain, the most appropriate kinematic model able to explain the observed tectono‐metamorphic architecture of the GHS is the duplexing model, or hybrid models which combine the duplexing model with another end‐member model.